2013
DOI: 10.1073/pnas.1304422110
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to capture and characterize the synaptic transcriptome

Abstract: Here we describe a strategy designed to identify RNAs that are actively transported to synapses during learning. Our approach is based on the characterization of RNA transport complexes carried by molecular motor kinesin. Using this strategy in Aplysia, we have identified 5,657 unique sequences consisting of both coding and noncoding RNAs from the CNS. Several of these RNAs have key roles in the maintenance of synaptic function and growth. One of these RNAs, myosin heavy chain, is critical in presynaptic senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 33 publications
2
53
0
Order By: Relevance
“…However, recent studies of RNA localization in mice, 5 Aplysia, 52 and proteomics analysis of signaling complexes at the synapse, [76][77][78] suggest an unprecedented molecular complexity of the synapse. Translational control by miRNAs at the synapse adds another layer to this complexity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies of RNA localization in mice, 5 Aplysia, 52 and proteomics analysis of signaling complexes at the synapse, [76][77][78] suggest an unprecedented molecular complexity of the synapse. Translational control by miRNAs at the synapse adds another layer to this complexity.…”
Section: Resultsmentioning
confidence: 99%
“…40 Knockdown experiments of ApMHC, actin-dependent molecular motor, and mRNA cargo of ApKHC1, also showed similar results on initiation and persistence of LTF. 52 Together, these studies suggest that during persistence of memory, synapses become autonomous with respect to transport from the cell body, and RNAs are stored at the synapses for later use.…”
Section: When and How Are The Synaptically Localizedmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the synaptic proteome is determined by proteins transported from the cell body and local synthesis of proteins at the synapses. Several studies have shown the identification and localization of RNAs at the synapse (9)(10)(11)(12). Comprehensive knowledge of the proteins that are actively targeted to synapses will help elucidate the dynamics of signal transduction at the synapse, as well as the molecules that are critical for the remodeling of synapses and formation of new synapses that accompany long-term memory storage.…”
mentioning
confidence: 99%
“…To identify actively transported proteins, we focused on the protein complexes associated with kinesins, molecular motor proteins that move from the cell body to distal neuronal processes and mediate the transport of various gene products (9,13). We considered that proteins associated with kinesins include both synaptic proteins and proteins localized to dendrites and axons.…”
mentioning
confidence: 99%